(untitled) (International conference on multidisciplinary science, 2025)
In newborns and children of the first months of life, biliary atresia occupies a leading place in the structure of liver and bile duct diseases. Biliary atresia was first described more than a century ago, but even now, issues of its timely diagnosis cause difficulties. At the same time, the effectiveness of surgical treatment depends on the age of the patient, which determines the exceptional importance of early diagnosis . There is no research method on the basis of which the diagnosis can be verified. Biliary atresia is established on the basis of characteristic clinical and laboratory manifestations, which change depending on the age of the child, as well as when excluding other diseases of the hepatobiliary system.